Community-Based Rehabilitation for Persons with Disabilities in Scheduled Tribes: A Theoretical and Policy Analysis - Rajvir (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Community-Based Rehabilitation (CBR) is a globally recognized strategy for empowering Persons with Disabilities (PwDs) by addressing their health, education, livelihood, and social inclusion needs. However, its implementation in marginalized communities, such as Scheduled Tribes (STs) in India, remains inadequate due to cultural, geographical, and policy-related challenges. This paper focuses on the theoretical and policy aspects of CBR for PwDs in Scheduled Tribes with a focus on cultural sensitivity, community participation, and technological innovation. The review of recent literature and policy frameworks will help to identify gaps in current CBR programs and recommend evidence-based suggestions for improvement in effectiveness. The results highlight the requirement for culturally responsive, community-led strategies to make development inclusive for PwDs in tribal areas.